Biodegradable poly(lactic acid) nanocomposites: synthesis and characterization - Li, Yonghui (Kansas State University, 2011)
Biobased polymers derived from renewable resources are increasingly important due to acute concerns about the environmental issues and limited petroleum resources. Poly(lactic acid) (PLA) is such a polymer that has shown great potential to produce biodegradable plastics. However, low glass transition temperature (Tg), low thermal stability, slow biodegradation rate, and high cost limit its broad applications. This dissertation seeks to overcome these limitations by reinforcing PLA with inorganic nanoparticles and low-cost agricultural residues. We first synthesized PLA nanocomposites by in situ melt polycondensation of L-lactic acid and surface-hydroxylized nanoparticles (MgO nanocrystals and TiO2 nanowires) and investigated the structure-property relationships. PLA grafted nanoparticles (PLA-g-MgO, PLA-g-TiO2) were isolated from the bulk nanocomposites via repeated dispersion/centrifugation processes. The covalent grafting of PLA chains onto nanoparticle surface was confirmed by Fourier transform infrared spectroscopy and thermalgravimetric analysis (TGA). Transmission electron microscopy and differential scanning calorimetry (DSC) results also sustained the presence of the third phase. Morphological images showed uniform dispersion of nanoparticles in the PLA matrix and demonstrated a strong interfacial interaction between them. Calculation based on TGA revealed that more than 42.5% PLA was successfully grafted into PLA-g-MgO and more than 30% was grafted into PLA-g-TiO2. Those grafted PLA chains exhibited significantly increased thermal stability. The Tg of PLA-g-TiO2 was improved by 7 °C compared with that of pure PLA. We also reinforced PLA with low-value agricultural residues, including wood flour (WF), soy flour (SF), and distillers dried grains with solubles (DDGS) by thermal blending. Tensile measurements and morphological images indicated that methylene diphenyl diisocyanate (MDI) was an effective coupling agent for PLA/WF and PLA/DDGS systems. MDI compatibilized PLA/WF and PLA/DDGS composites showed comparable tensile strength and elongation at break as pure PLA, with obviously increased Young’s modulus. Increased crystallinity was observed for PLA composites with SF and DDGS. Such PLA composites have similar or superior properties compared with pure PLA, especially at a lower cost and higher biodegradation rate than pure PLA. The results from this study are promising. These novel PLA thermoplastic composites with enhanced properties have potential for many applications, such as packaging materials, textiles, appliance components, autoparts, and medical implants.
Keywords: Poly(lactic acid); Nanoparticles; Nanocomposites; Composites; Biodegradable; Materials Science (0794); Polymer Chemistry (0495)